CRIMINAL LINGUISTICS AND LEGAL TERMINOLOGY (World Bulletin of Management and Law, 2024)
Criminal linguistics is a rapidly developing area of linguistics, which deals with the analysis of texts and the determination of their legal significance within the framework of a criminal case. This article analyzes the theoretical foundations of criminological research, its connection with legal terminology and its application in real life. In particular, the linguistic features of court documents, contracts, investigation reports and criminal correspondence are studied. The study highlights the importance of the integration of legal analysis and linguistic methods, revealing the role of language in the investigation of crimes